Konsep Bumi Datar: Analisis Historis, Media Sosial, dan Bukti Ilmiah - Fatimah Nur Aliyah (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
This study examines the phenomenon of flat Earth belief persisting in modern society, despite widespread scientific evidence that the Earth is round. The aim of the study was to understand why this theory persists using a multidisciplinary approach that includes historical reading, social media analysis, and scientific evidence. Historical reading helps identify the context and roots of this belief, and how it has evolved over time. Social media analysis reveals the important role of filter bubbles and echo chambers in the spread and amplification of flat Earth theory, where algorithms and the digital environment limit exposure to information that supports a particular view. Scientific evidence provides a strong empirical basis for rejecting flat Earth theory, but challenges remain in conveying scientific evidence in a way that is understandable and accepted by the wider public. The study findings suggest that flat Earth belief is influenced by complex social and psychological factors as well as the impact of social media in amplifying this belief. This study underscores the need for more effective approaches to improving science literacy and addressing the spread of misinformation in the digital age. Strategies that involve collaboration between disciplines are needed to address these challenges and improve public understanding of science